Determinants of Fertility in Rural Women of Fars Province: Actual and Ideal Fertility and Fertility Intention - Afshan Javadi; Aliyar Ahmadi; Fariba Moradi; Zohreh Balaghi; Nooshin Zarei (Shiraz University of Medical Sciences, 2017)
Background: During the last two decades, fertility has declined to replacement level in rural areas of Iran. The current study investigated the determinant factors of actual and ideal fertility, and fertility intention in rural women of Fars province.Method: This is a cross-sectional study. The sample comprised 1301 rural married women aged 15 to 49 years in Fars province. Data were gathered in 2015 using structured questionnaires. Statistical analysis was run on STATA software, version 12.0. The semi-partial correlation was run to show the unique effect of each variable while controlling all the other variables. Finally, a multiple regression model was run with a significance level of 0.05. Results: The means(±SD) of actual and ideal fertility were 2.11±(1.32) and 2.81±(0.96), respectively, and for fertility intention it was 2.92±)1.00(. Age was the most determinant factor of actual, ideal fertility and fertility intention. The second effective factor was age at first birth. The determination coefficient for the actual fertility model showed that 62.1% of the variance in actual fertility was explained by age, age at first birth, woman's education, and use of contraceptive methods. For ideal fertility and fertility intention, about 16.2% and 27.5% of the variance were explained by the independent variables, respectively.Conclusion: As a result of the rise in education and social position of younger women, the opportunity cost of having a child is more effective than ever. Therefore, fertility incentive policies could not be effective in increasing fertility, even in among rural population.